Development of Hand Gestures Controlled Lawn Mower Cleaning Machine: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
A lawn mower is a cleaning tool commonly used to cut grasses. Some lawn mowers havebeen used in the industry, including the push mower, ride-on mower, rotary mower, and self-propelled mowers. This project research aims to develop an innovative lawn mower machinethat performs tasks and helps reduce the cost of help for cutting grass in their lawn area. Thismachine is a more environmentally friendly alternative to gas-powered products.The overall testing accuracy of this hand gestures-controlled lawn mower cleaning machinewas evaluated with 100%, and given the overall mean score of 3.57, it was interpreted asstrongly agreeable. These results indicate that all of the respondents, which are the gardenersand homeowners of Vista Verde North Executive Village, shared a common high scoreevaluation.Therefore, the research shows that the components used, including the Arduino Nano as amicrocontroller and the MPU6050 Gyroscope sensor, are effective materials in building theproduct.
Keywords: Engineering; Computer Science